The Dilemma of Settlement of Sharia Economic Disputes in the Religious Courts - Asep Syarifuddin Hidayat (Mimbar Agama dan Budaya, 2022)
This article analyzes the difficulties in resolving Sharia economic disputes in the Religious Courts and offers suggestions for improving the efficacy of these dispute resolutions. This study identified many obstacles, such as the limited knowledge and comprehension of religious judges regarding Sharia economic law, the Complexity of disputes and difficult-to-understand evidence, and the slow settlement process and high costs. Through analysis and a review of the relevant literature, this article offers several suggestions for overcoming these obstacles. The first recommendation is to increase religious judges' comprehension of sharia economic law through intensive training and education programs. The second recommendation is to enhance cooperation between Religious Courts and Islamic financial institutions to make dispute resolution more effective. To improve the quality of dispute resolution, the third recommendation is the development of education and training programs for mediators and arbitrators. Utilizing technology in the dispute resolution process to improve efficiency and accessibility is the final recommendation. This article has significant implications for the Religious Courts' Sharia economic dispute resolution system. By implementing the proposed guidance, the resolution of Sharia financial disputes is anticipated to become more efficient, equitable, and consistent with the principles of sharia economic law. Abstrak: Artikel ini menganalisis kesulitan yang terlibat dalam penyelesaian sengketa ekonomi syariah di Pengadilan Agama dan menawarkan saran untuk meningkatkan efektivitas penyelesaian sengketa tersebut. Studi ini mengidentifikasi sejumlah kendala, seperti keterbatasan pengetahuan dan pemahaman hakim agama tentang hukum ekonomi syariah, kompleksitas sengketa dan bukti yang sulit dipahami, serta proses penyelesaian yang lamban dan biaya yang tinggi. Melalui analisis dan kajian literatur yang relevan, artikel ini menawarkan beberapa saran untuk mengatasi kendala tersebut. Rekomendasi pertama adalah meningkatkan pemahaman hakim agama terhadap hukum ekonomi syariah melalui program pelatihan dan pendidikan yang intensif. Rekomendasi kedua adalah meningkatkan kerjasama antara Pengadilan Agama dan lembaga keuangan syariah agar penyelesaian sengketa lebih efektif. Untuk meningkatkan kualitas penyelesaian sengketa, rekomendasi ketiga adalah pengembangan program pendidikan dan pelatihan mediator dan arbiter. Memanfaatkan teknologi dalam proses penyelesaian sengketa untuk meningkatkan efisiensi dan aksesibilitas merupakan rekomendasi akhir. Pasal ini berimplikasi signifikan terhadap sistem penyelesaian sengketa ekonomi syariah di Pengadilan Agama. Dengan melaksanakan rekomendasi yang diajukan, diharapkan penyelesaian sengketa ekonomi syariah menjadi lebih efisien, berkeadilan, dan sejalan dengan prinsip-prinsip hukum ekonomi syariah.Kata kunci: Sengketa Ekonomi Syariah; Pengadilan Agama; Penyelesaian Sengketa.